2016
DOI: 10.3329/bmj.v44i1.26348
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthetic and analgesic eects of adding fentanyl to bupivacaine-lignocaine mixtures in supraclavicular brachial plexus block – a comparative study with or without fentanyl

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Sert et al 22 also demonstrated prolongation of the motor and sensory block as well as the time of first analgesic requirement when fentanyl was added to articaine in axillary blocks. In a study conducted by Zainab et al 23 in which 100 mcg fentanyl was added to lignocaine-bupivacaine mixtures in supraclavicular brachial plexus block, the mean onset of sensory and motor block was significantly early and the duration of analgesia was significantly longer. The patients with added fentanyl had no pain up to 4 hours; first pain (VAS >4) reporting was around 5 hours, and the worst pain was experienced after 8 hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sert et al 22 also demonstrated prolongation of the motor and sensory block as well as the time of first analgesic requirement when fentanyl was added to articaine in axillary blocks. In a study conducted by Zainab et al 23 in which 100 mcg fentanyl was added to lignocaine-bupivacaine mixtures in supraclavicular brachial plexus block, the mean onset of sensory and motor block was significantly early and the duration of analgesia was significantly longer. The patients with added fentanyl had no pain up to 4 hours; first pain (VAS >4) reporting was around 5 hours, and the worst pain was experienced after 8 hours.…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed that the addition of fentanyl causes significantly early onset of anesthesia and longer duration of analgesia without any side effects. 23…”
Section: Discussionmentioning
confidence: 99%
“…Large volumes of local anesthetics required to produce desirable effects may result in systemic side effects. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%